The Role of ChatGPT in Enhancing the Information Search and Decision-Making Process of Travellers - Frans Sudirjo; Prety Diawati; Yasir Riady; Abu Muna Almaududi Ausat; Suherlan Suherlan (Politeknik Ganesha Medan, 2023)
In today's digital era, the internet and technology are growing rapidly. One of the significant technological advances is ChatGPT which is able to accelerate the process of information search and decision making in the world of tourism. This research aims to discuss the role of ChatGPT in improving the process of information search and decision making of tourists. This research is qualitative in nature. The techniques used to obtain information involve careful observation and meticulous note-taking, followed by analytical procedures such as data reduction, visualisation, and inference. This study arrives at the conclusion that in today's digital era, artificial intelligence technologies such as ChatGPT have an important role to play in improving travellers' information search and decision-making process. ChatGPT can provide recommendations, information, and customer service quickly and effectively, thus helping travellers to plan their trips more easily and efficiently.